MODEL FOR EVALUATING THE ECONOMIC EFFICIENCY OF INVESTMENT PROJECTS: ARCHITECTURE AND MAIN ASPECTS OF APPLICATION - Mackevičius, Jonas; Tomaševič, Vladislav (Ekonomika, 2011)
Evaluation of investment projects is a complex multilateral process which also entails a great responsibility as its results form a basis for adopting investment decisions. These decisions, to a large extent, depend on the reliability and justification of the evaluation results: therefore, the process must be based on clear logic, acceptable assumptions and the duly selected methods that have been tested in practice. The paper contains an overview of the main principles of investment projects’ evaluation and a detailed analysis of the main requirements for the model architecture and its evaluation process.The authors propose a model for evaluating the economic efficiency of investment projects that has been described in detail and tested in practice. The model consists of a coherent evaluation scheme made of three phases and detailed algorithms of internal procedures. Such an architecture of the model enables a comprehensive analysis of investment projects of different types and a validation of the objectivity of evaluation results.